PHYGITAL INTERFACE DESIGN FOR SOCIOEMOTIONAL: A QUALITATIVE CHILD-COMPUTER INTERACTION STUDY - Nurasilah Osman; Tengku Siti Meriam Tengku Wook; Maizatul Hayati Mohamad Yatim; Nor Masharah Husain; Norly Jamil; Nadia Akma Ahmad Zaki (YHMM PUBLISHING, 2026)
Phygital learning environments, which merge tangible play with real-time digital feedback, are gaining attention in early childhood education, yet their socioemotional impact remains underexplored. Existing studies on phygital systems primarily emphasize cognitive or usability outcomes, leaving limited empirical evidence on how interface design shapes children’s emotional and social behaviours. This study investigated how phygital interface design supports socioemotional competencies among Malaysian preschoolers. Fifteen children aged 5-6 from two preschools engaged with Osmo phygital games involving both individual and collaborative play. Video recordings, observation checklists, and field notes were analysed using reflexive thematic analysis, supported by triangulation and peer debriefing to ensure credible behavioural interpretation. Findings show socioemotional behaviours like self-awareness, self-control, self-concept, self-confidence, and social skills with empathy emerge from design features such as hybridization, tangibility, interactivity, multisensory feedback, contextual relevance, personalization, and collaboration. Embodied emotional feedback enhanced self-regulation, hybrid tangible-digital play promoted motivation and confidence, and collaborative interaction strengthened empathy and peer support. This study positions phygital interfaces as emotionally responsive systems that integrate affective, cognitive, and social learning, offering evidence-based design implications for child-centred educational technologies.